Menggunakan SPADE Algorithm Untuk Sistem Rekomendasi Film - Aldy Noah; Rolly Intan; Alvin Nathaniel Tjondrowiguno (Jurnal Infra, 2020)
Nowadays, internet has become main thing in everyday life. This cause the consumption of entertainment media can be done anywhere and everywhere. One of the entertainments we enjoy is movie. With the increasing popularity of streaming media, movie fans also increase.Because of the increase of movie fans, the need of recommendation system that can recommend movie to its user also rise. System recommendation for movie is a complicated thing because of considerable amount of movie and movie fans.Sequence pattern mining is one of data mining method that can be used to gain frequent pattern from a set of data. Frequent pattern is a series of items that forms a pattern in a set of data. SPADE is one of the methods to find frequent sequence. The advantage of using SPADE is that speed in which SPADE can find frequent sequence in a data set. The benefit of using SPADE algorithm is in the speed of the algorithm to find frequent sequence. The resulting frequent sequence then can be used as a basis for recommendation to the user.